2014
DOI: 10.1093/jac/dku177
|View full text |Cite
|
Sign up to set email alerts
|

Doripenem population pharmacokinetics and dosing requirements for critically ill patients receiving continuous venovenous haemodiafiltration

Abstract: This is the first paper describing the pharmacokinetics/pharmacodynamics of doripenem in critically ill patients with AKI receiving CVVHDF. A dose of 500 mg intravenously every 8 h was appropriate for our CVVHDF settings for infections caused by susceptible bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
4
30
1
1
Order By: Relevance
“…Furthermore, concentration drops below 4 mg/liter during steady state could be observed in 15.2% of the cases. (3,4). The sieving coefficients observed in our study differed dramatically from those reported by Cirillo et al A possible explanation for the difference between prefilter/ postfilter clearance and sieving coefficient-dependent clearance could be adsorption of doripenem to the filter membrane.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, concentration drops below 4 mg/liter during steady state could be observed in 15.2% of the cases. (3,4). The sieving coefficients observed in our study differed dramatically from those reported by Cirillo et al A possible explanation for the difference between prefilter/ postfilter clearance and sieving coefficient-dependent clearance could be adsorption of doripenem to the filter membrane.…”
Section: Resultscontrasting
confidence: 92%
“…A two-compartment model with linear elimination was best for describing the pharmacokinetics of doripenem in plasma, which is consistent with findings from previous population pharmacokinetic studies (4,11). The estimated pharmacokinetic parameters, as well as the bootstrap results, are shown in Table 4.…”
Section: Resultssupporting
confidence: 87%
“…First, we did not include patients who had septic shock or who were on continuous renal replacement therapy. Such factors could alter the PK profiles of doripenem (10,46). Second, our data do not include doripenem concentrations at the target site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This enables development of mathematical models that describe PK variability in terms of most relevant RRTrelated and clinical covariates. The more precise estimation of PK parameters enables a more precise prediction of dosing requirements [11,12]. However, even the few available population PK models do not account for the full range of covariates and would require standardization in terms of RRT modalities and operational settings to ensure wide application.…”
Section: Antibiotic Dosing In Critically Ill Patients Receiving Renalmentioning
confidence: 99%